TECHNIQUE AND TECHNOLOGY OF VISUAL CONTROL OF INNER SURFACES OF CASTINGS AND MOLDS - E. I. Marukovich; A. P. Markov; A. V. Kononov; D. A. Gorbunov; E. V. Belanko (Литьë и металлургия)
The peculiarities of physical-optical conversions in visual control of internal surfaces of castings and molds using lightguiding, video and optoelectronic technique are examined.